Estruturas de investimento em startups atuantes no segmento de finanças descentralizadas - Kencis, Rodrigo de Carvalho (2023)
This dissertation discusses investment structures in startups operating in the decentralized finance sector. Currently holding second place in the decentralized finance market, Brazil has been standing out for the projects being developed on its territory and for the volume of investments received by startups operating in the DeFi market. Throughout this work, we sought to demonstrate the evolutionary process of startups, from the idea's conception to its implementation, and to present the path taken by founders and investors, culminating in the celebration of an investment instrument. In addition to the theoretical exposition, this dissertation aimed to bring the investment process into practical conception by exposing contractual clauses commonly used in instruments signed for this purpose. This work expects to stimulate the deepening of the study of the decentralized finance market, which is currently under legal and regulatory scrutiny from the Brazilian Central Bank and the Brazilian Securities and Exchange Commission